Menemukan Makna Tawakal di Tengah Modernitas: Refleksi atas Kisah Kepasrahan Nabi Ismail dalam QS. Ash-Shaffat 102–107 - Awalia Kholifatur Riska; Ahmad Nurrohim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to explore the meaning of tawakal in the story of Prophet Ismail as described in Surah Ash-Shaffat verses 102–107 and to examine its relevance to modern human life. Through a thematic interpretation (tafsir maudhu‘i) and a comparative analysis between classical and contemporary interpretations, this study finds that tawakal is not merely an attitude of surrender to Allah's will, but a form of spiritual awareness that unites effort and submission. Classical exegetes such as al-Tabari, Ibn Kathir, and al-Qurtubi interpret this story as the pinnacle of obedience and total surrender of a servant to Allah's commands. Meanwhile, contemporary exegetes such as Quraish Shihab and Sayyid Quthb emphasize the reflective and psychological dimensions, that tawakal is a spiritual force that fosters inner peace amid the pressures of modern life. Research findings indicate that the value of tawakal has profound significance as a moral principle, social ethic, and spiritual therapy capable of restoring balance between rationality and faith in facing the existential crises of modern humanity.